Giant Overlap between the Magnetic and Superconducting Phases of CeAu_{2}Si_{2} under Pressure - Z. Ren; L. V. Pourovskii; G. Giriat; G. Lapertot; A. Georges; D. Jaccard (Physical Review X, 2014)
High pressure provides a powerful means for exploring unconventional superconductivity which appears mostly on the border of magnetism. Here, we report the discovery of pressure-induced heavy-fermion superconductivity up to 2.5 K in the antiferromanget CeAu_{2}Si_{2} (T_{N}≈10  K). Remarkably, the magnetic and superconducting phases are found to overlap across an unprecedentedly wide pressure interval from 11.8 to 22.3 GPa. Moreover, both the bulk T_{c} and T_{M} are strongly enhanced when increasing the pressure from 16.7 to 20.2 GPa. T_{c} reaches a maximum at a pressure slightly below p_{c}≈22.5  GPa, at which magnetic order disappears. Furthermore, the scaling behavior of the resistivity provides evidence for a continuous delocalization of the Ce 4f electrons associated with a critical end point lying just above p_{c}. We show that the maximum T_{c} of CeAu_{2}Si_{2} actually occurs at almost the same unit-cell volume as that of CeCu_{2}Si_{2} and CeCu_{2}Ge_{2}, and when the Kondo and crystal-field splitting energies become comparable. Dynamical mean-filed theory calculations suggest that the peculiar behavior in pressurized CeAu_{2}Si_{2} might be related to its Ce-4f orbital occupancy. Our results not only provide a unique example of the interplay between superconductivity and magnetism, but also underline the role of orbital physics in understanding Ce-based heavy-fermion systems.